Supramolecular solubilization of cyclodextrin-modified carbon nano-onions by host-guest interactions - Wajs, Ewelina (Langmuir : the ACS journal of surfaces and colloids, 2015)
Small carbon nano-onions (CNOs, 6-12 shells) were prepared in high yields and functionalized with carboxylic groups by chemical oxidation and reacted with βCD-NH2 to yield CNOs decorated with βCDs. A biocompatibile dextran polymer with graphted ferrocene groups was employed for the supramolecular self-assembly on the βCD-CNO surfaces. The βCDs act as hosts and the polymer ferrocene groups as guests (Fc-Dex) by the formation of inclusion complexes. After their assembly these nanostructures were soluble in aqueous solutions. The resulting product was characterized by transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and FT-IR and Raman spectroscopies. Moreover, the deposition of successive layers on the surface of the particles was monitored using DLS measurements and zeta potentials. Through-space interactions between the Fc moieties and the CNO cores and the influence of an additional dextran-βCD outer layer were measured electrochemically